Kajian Konseptual Teknologi Constructed Wetlands sebagai Sistem Pengolahan Limbah Cair Permukiman di Kelurahan Pampang Kota Makassar - Baso, Darwis (Jurnal Serambi Engineering, 2026)
Domestic wastewater management at the neighborhood scale remains a significant environmental challenge, particularly in areas with limited sanitation infrastructure. Pampang Village, Makassar City faces constraints related to the suboptimal performance of domestic wastewater treatment systems, which may degrade residential environmental quality and contaminate surrounding water bodies. Constructed wetlands (CW) have emerged as nature-based wastewater treatment technologies offering sustainable and locally adaptive sanitation alternatives. This study aims to examine the conceptual suitability of CW as a domestic wastewater treatment system at the neighborhood level in Pampang Village, Makassar City. The research method is based on a literature review and conceptual analysis of CW working principles, system types and characteristics, and their suitability in terms of technical, operational, environmental, and social aspects. The results indicate that CW demonstrate a high level of suitability for implementation at the neighborhood scale. Domestic wastewater with moderate organic loads allows CW to operate effectively through the integration of physical, chemical, and biological processes. Design flexibility, particularly in vertical-flow and hybrid systems, enhances adaptability to land limitations, while low energy requirements and operational simplicity support community-based implementation.